Meningkatkan Daya Dukung Pondasi Tiang Pancang Gedung Abipraya Mojo Kabupaten Kediri Menggunakan Metode Begemann - Arif Fathur Rohman; Edy Gardjito; Agata Iwan Candra; Andri Dwi Cahyono (Faculty of Engineering, Kadiri University, 2021)
The foundation is a lower structural element that serves to with stand the load of the upper structure. Pile foundation is one type of deep foundation, which is widely used in the construction of buildings. Pile foundation used in hard soil cases is located at a very deep depth. Abipraya Building is a building located in kediri regency which later functioned as a rural office. This study aims to increase the carrying capacity of pile foundation in the abipraya building project using the begemann method. Calculations carried out include the calculation of loading, carrying capacity, buckling factor and determination of foundation point. Based on the calculations obtained the results of axial load (sigma Vertical Ultimate) Σνυ of 99.70. with a single-pole carrying capacity of 38.89 tons and a group pole carrying capacity of 117,917 tons. These results will be planned the foundation of the stake with a diameter of 30 with a depth of 8 meters, amounting to 4 poles. Calculation factor buckling results in 194.14 kg/cm2 smaller than the allowed maximum 2400 kg/cm2. Thus, with the known components of the planning of the pile foundation, it can be used as a reference in the construction of the abipraya building.